Toponimi Wilayah Pati dan Jepara: Jejak Air dalam Nama Tempat Abad ke-17 - Nina Witasari; Wahyu Setyaningsih; Halim Sukma Aji; Riza Dinda Agnesia (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This study explores toponymy in the Pati and Jepara regions by tracing water-related elements in place names from the 17th century, linking them to landscape changes around the Muria Strait. Using a geohistorical approach, the research reconstructs the dynamics of the northern Central Java coastal landscape, focusing on shifts in water boundaries that once separated Mount Muria from the island of Java. The study combines toponymic analysis with hydrological, geological, and historical archival data to trace the evolving function and meaning of aquatic spaces in local communities. This process also influenced spatial transformations and patterns of settlement. The toponymic findings reveal that several place names in Pati and Jepara contain references to water. Their distribution patterns correlate with remnants of ancient river flows, marshlands, and waterways that have since dried up or changed form. Geological evidence indicates significant sedimentation in the Muria Strait from the late 16th century onward, gradually leading to the merging of Muria Island with Java’s mainland. By connecting toponymic patterns with natural transformations, this study affirms that water served not only as a physical element but also as a cultural symbol, encoding traces of local ecological change. These findings contribute to interdisciplinary research on coastal landscape evolution and underscore the importance of place names as a source of geohistorical information in Indonesia.